Persepsi Mahasiswa terhadap Instruktur Sebaya pada Praktikum Pendengaran di Laboratorium Ilmu Faal Dakultas Kedokteran Universitas Gadjah Mada - Gandes Endah Pakarti; Widya Wasityastuti; Yayi Suryo Prabandari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background:The traditional learning method applies at Physiology Laboratory of Faculty of Medicine at Universitas Gadjah Mada (UGM) is considered ineffective for the lecturers in managing the students. Moreover, the students perceive that their needs are not adequately accommodated by the lecturers. This downside can be resolved by an alternative learning method which provides conducive, active, creative, effective and enjoyable learning environment called peer assisted learning method. This study is aimed at discovering the students’ perceptions on peer assisted learning method and acquiring the students’ feedback and expectations on the effectiveness of peer-teaching method implementation.Method:The study used cross-sectional design of descriptive research.Results:From the questionnaire analysis with 150 respondents, 90 students of regular program and 60 students of international program, the result according to the frequencies of student perception were: 1) factor 1 were 45.8 % for very high category, 29.8 % for high category, 23.7 % for medium category, 0,8 % for very low category and 0 % for low category; 2) factor 2 were 45 % for high category,41.2 % for medium category,11.5 % for very high category,1.5 % for low category and 0.8 % for very low category; 3) factor 3 were 51.9 % for very high category, 31.3 % for high category,16.0 % for medium category,0.8% for very low category and 0% for low category; 4) factor 4 were 47.3 %for high category, 31.3 % for very high category,19.1 % for medium category,1.5 % for low category and 0.8% for very low category. There was no difference in perception between the students of regular and international program. Responses to open questions and FGD show a variety of students’ feedback and expectation on the peer assisted learning method.Conclusion:The students have shown positive perception on peer assisted learning as a learning method. The peer instructors required in Implementing this model are those students with good communication skill, confirmed academic qualification and capability in managing their fellow students’ learning.